The new dynamics of winning : gain the mind-set of a champion for unlimited success in business and life - Waitley, Denis (W. Morrow, 1993)
Recognized as an authority on high-level achievement, Denis Waitley has studied and counseled leaders in every field - from top executives of Fortune 500 companies to Super Bowl champions. The author of the all-time bestselling personal development audio program (more than six million cassettes sold to date!), Waitley has helped millions throughout the world realize their potential - and become winners. In The New Dynamics of Winning, Waitley explains, for the first time ever, the amazing similarities in the mental strategies of business champions and sports champions. Teaching by example, he evokes sports winners including Jackie Joyner-Kersee, Greg LeMond, Gail Devers, Mary Lou Retton, and Bill Toomey, and compares them to winners in other fields like Carol Moseley Braun, Bill Gates, Meryl Streep, and Ray Kroc.